2023
DOI: 10.1101/2023.07.28.550971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hallucination proneness alters sensory feedback processing in self-voice production

Abstract: Background: Sensory suppression occurs when hearing ones self-generated voice, as opposed to passively listening to ones own voice. Quality changes of sensory feedback to the self-generated voice can increase attentional control. These changes affect the self-other voice distinction and might lead to hearing non-existent voices in the absence of an external source (i.e., auditory verbal hallucinations (AVH)). However, it is unclear how changes in sensory feedback processing and attention allocation interact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Previous studies probing prediction of sensory feedback to the self-voice reported no N100 suppression effect in voice hearers with a psychotic disorder [106,107] whereas non-clinical voice hearers or high HP individuals showed a reversed N100 suppression effect [38,39,108]. These studies either used group differences [107] or hypothesized a linear relationship between HP and sensory feedback processing/attentional control, measured by the N100 suppression effect, using LMMs [39,108]. Future studies should consider that individuals on the postulated HP severity continuum (voice hearers with psychotic disorder, at high-risk of psychosis/prodromal and non-clinical voice hearers) may show a nonlinear relationship with the N100 suppression effect.…”
Section: Hallucination Proneness Sensory Feedback Processing and Atte...mentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies probing prediction of sensory feedback to the self-voice reported no N100 suppression effect in voice hearers with a psychotic disorder [106,107] whereas non-clinical voice hearers or high HP individuals showed a reversed N100 suppression effect [38,39,108]. These studies either used group differences [107] or hypothesized a linear relationship between HP and sensory feedback processing/attentional control, measured by the N100 suppression effect, using LMMs [39,108]. Future studies should consider that individuals on the postulated HP severity continuum (voice hearers with psychotic disorder, at high-risk of psychosis/prodromal and non-clinical voice hearers) may show a nonlinear relationship with the N100 suppression effect.…”
Section: Hallucination Proneness Sensory Feedback Processing and Atte...mentioning
confidence: 92%
“…Furthermore, because of the small number of voice hearers with a psychotic disorder we were unable fully to explore the putative psychosis continuum. Previous studies probing prediction of sensory feedback to the self-voice reported no N100 suppression effect in voice hearers with a psychotic disorder [106,107] whereas non-clinical voice hearers or high HP individuals showed a reversed N100 suppression effect [38,39,108]. These studies either used group differences [107] or hypothesized a linear relationship between HP and sensory feedback processing/attentional control, measured by the N100 suppression effect, using LMMs [39,108].…”
Section: Hallucination Proneness Sensory Feedback Processing and Atte...mentioning
confidence: 99%
“…Based on these aspects, it is likely that the perceptual discriminability among the five types of self-vocalizations varying in pleasure content used here might have been low. Further, using the same sample of participants and design but a selfvoice continuum from neutral to angry yielded a significant global N100 suppression effect (Duggirala et al, 2023). Hence, the question arises as to why similar effects did not emerge as a function of a continuum manipulation for positive vocal emotion expressions.…”
Section: Discussionmentioning
confidence: 93%
“…Participants in the current study did not exhibit a complete sense of ownership ("my voice or someone else's voice") and agency ("feeling associated with the sensory outcome of one's voluntary action") of their own 100% pleasure voice. The sense of ownership was lower for the 100% pleasure stimuli compared to the 100% angry self-voice ( (Herbert, Herbert, Ethofer, & Pauli, 2011;Yoshie & Haggard, 2013); supplementary figure 1C and supplementary figure 1C of Duggirala et al, 2023)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation